High Grade Glioma Mimicking Voltage Gated Potassium Channel Complex Associated Antibody Limbic Encephalitis - Dilan Athauda; R. S. Delamont; E. De Pablo-Fernandez (Case Reports in Neurological Medicine)
Though raised titres of voltage gated potassium channel (VGKC) complex antibodies have been occasionally associated with extracranial tumours, mainly presenting as Morvan's Syndrome or neuromyotonia, they have not yet been reported to be associated with an intracranial malignancy. This is especially important as misdiagnosis of these conditions and delay of the appropriate treatment can have important prognostic implications. We describe a patient with a high grade glioma presenting with clinical, radiological, and serological features consistent with the diagnosis of VGKC antibody associated limbic encephalitis (LE). This is the first association between a primary brain tumour and high titre of VGKC complex antibodies. Clinicoradiological progression despite effective immunosuppressive treatment should prompt clinicians to look for alternative diagnoses. Further studies to elucidate a possible association between VGKC complex and other surface antigen antibodies with primary brain tumours should be carried out.